2021
DOI: 10.21037/atm-20-5044
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs: novel players in the pathogenesis of polycystic ovary syndrome

Abstract: Long non-coding RNAs (lncRNAs) are a class of transcripts (>200 nucleotides) lacking proteincoding capacity. Based on the complex three-dimensional structure, lncRNAs are involved in many biological processes and can regulate the expression of target genes at chromatin modification, transcriptional and post-transcriptional levels. LncRNAs have been studied in multiple diseases but little is known about their role(s) in polycystic ovary syndrome (PCOS), the most common endocrinological disorder in reproductivea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Furthermore, epigenetic modifications in the pathogenesis of PCOS have come into the focus of interest, and changes in DNA methylation have been observed in the serum, ovaries, hypothalamus, skeletal muscle and adipose tissue of PCOS patients [ 101 , 102 ]. Transcriptomics allow the identification of aberrantly expressed genes in the granulosa or cumulus cells of women with PCOS and have already revealed genes with altered expressions, including non-coding RNAs, such as miRNAs and lncRNAs, which might contribute to ovarian dysfunction [ 103 , 104 ]. Finally, proteomics are used, e.g., to identify novel protein biomarkers in the serum or follicular fluid (FF) of PCOS patients.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…Furthermore, epigenetic modifications in the pathogenesis of PCOS have come into the focus of interest, and changes in DNA methylation have been observed in the serum, ovaries, hypothalamus, skeletal muscle and adipose tissue of PCOS patients [ 101 , 102 ]. Transcriptomics allow the identification of aberrantly expressed genes in the granulosa or cumulus cells of women with PCOS and have already revealed genes with altered expressions, including non-coding RNAs, such as miRNAs and lncRNAs, which might contribute to ovarian dysfunction [ 103 , 104 ]. Finally, proteomics are used, e.g., to identify novel protein biomarkers in the serum or follicular fluid (FF) of PCOS patients.…”
Section: Polycystic Ovary Syndromementioning
confidence: 99%
“…FF is filled with a variety of vesicles and molecules, including exosomes, which largely contribute to follicular development and ovum maturation [ 8 ]. Studies have proven that some nucleic acids and proteins in FF are closely involved in follicular glucose metabolism, lipoprotein metabolism, cell proliferation and other processes in patients with PCOS [ 9 11 ]. FF-derived exosomes are the main carriers of these nucleic acids and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are a class of transcripts (>200 nucleotides) lacking protein-coding capacity, and they function as competitive endogenous RNAs (ceRNAs) and are significantly correlated with some clinical phenotypes in PCOS [ 30 ]. Previous studies have found that the expression levels of RDH10-AS1, NARF-IT1, AC090617.1, MZF1-AS1, AC009495.2, LINC01564, AQP4-AS1, L34079.3, OSBPL10-AS1, PIK3CD-AS2, LINC01181, and LINC00907 were reduced in PCOS [ 18 ].…”
Section: Discussionmentioning
confidence: 99%